Predicting Postoperative Mortality in Head Injury Patients: Evaluating the Accuracy of Rotterdam Score - Fadhli Aufar Kasyfi; Agung Muda Patih; Erial Bahar (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2025)
Introduction: Head injury remains a leading cause of mortality and morbidity globally, necessitating accurate prognostic tools to guide clinical decision-making and inform patient outcomes. Rotterdam Score, a computed tomography (CT)-based scoring system, has shown promise in predicting mortality in head injury patients. This study aimed to evaluate the accuracy of the Rotterdam Score in predicting postoperative mortality in head injury patients undergoing surgery. Methods: A retrospective analysis was conducted on 56 head injury patients who underwent surgery at Dr. Mohammad Hoesin General Hospital, Palembang, between December 2023 and November 2024. Patient demographics, clinical characteristics, and CT scan findings were collected. Rotterdam Score was calculated for each patient, and its accuracy in predicting postoperative mortality was assessed using receiver operating characteristic (ROC) curve analysis. Results: The study cohort comprised 37 (66.1%) males and 19 (33.9%) females, with a mean age of 31.8 ± 21.6 years. Mild head injury was the most common Glasgow Coma Scale (GCS) classification (42.9%). The overall mortality rate was 17.8%. ROC curve analysis revealed an area under the curve (AUC) of 0.953 for the Rotterdam Score, with an optimal cut-off value of 4.5. Rotterdam Score demonstrated a sensitivity of 80%, specificity of 97.8%, positive predictive value (PPV) of 88.8%, and negative predictive value (NPV) of 95.7% in predicting postoperative mortality. Conclusion: The Rotterdam Score is a highly accurate predictor of postoperative mortality in head injury patients undergoing surgery. Its CT-based assessment allows for rapid and objective prognostication, aiding clinicians in risk stratification and treatment planning. Further research with larger and more diverse populations is warranted to validate these findings and establish the generalizability of Rotterdam Score across different healthcare settings.